Haul Music : transnationalism and musical performance in the Saharaui refugee camps of Tindouf, Algeria,Transnationalism and musical performance in the Saharaui refugee camps of Tindouf, Algeria - Gimenez Amoros, Luis (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2012)
The thesis presents ethnographic data and musical analysis (in the form of transcriptions) of Haul music which is the music style performed by Bedouin societies in Trab el Bidan region (Mauritania, Western Sahara, northern Mali, southern Algeria and northern Morocco). It is based on field research undertaken in Algeria in 2004-05 in the refugee camps of Tindouf, Algeria, where Saharaui people (a Bedouin society)live in exile. This research is unique and original as Haul has not, until now, been explored in depth by any scholar. My research on Haul reveals that the changes in Saharaui music in the refugee camps of Tindouf reflect changes in the musical traditions of Bedouin societies as whole; changes that can be traced to the revolution which occurred in Western Sahara in 1975, and changes that are a result of the migrations and life in exile that followed. I argue that these changes occurred due to the transnational experiences undergone by Saharaui people in their forced exile (caused by the Moroccan state) from their homeland in Western Sahara to Algeria. Further, I assert that the invocation of memory in Bedouin musical styles is evidence of past musical practices being retained in contemporary Haul performance, although other musical changes are similarly in progress.
Keywords: Bedouins -- Music -- Research; Sahrawi (African people) -- Migrations; Social change -- Arab countries; Arab countries -- Social life and customs; Civilization, Arab